POSTER SEBAGAI MEDIA EDUKASI PENGGUNAAN MASKER PADA IBU-IBU PKK DI DUSUNDUSUN JAGALAN KLATEN - Septian Emma Dwi Jatmika; Hilmi Amallia Putri Siswanto (Jurnal Kesehatan dan Pengelolaan Lingkungan, 2021)
Based on interviews with PKK members, it was found that the health proto-col that the residents of Jagalan Hamlet often violated was the use of masks. One of the efforts to increase knowledge is to conduct health education using poster media. This study was conducted to determine the effect of providing education using poster media on PKK mothers' knowledge level. This research is a quasi-experimental research with one group pretest post-test design. The research sample was taken by purposive sampling with a total of 16 people who are members of the PKK. Research data were analy-zed using the Wil-Coxon test. The results showed a significant difference in the knowledge level before and after being given education using poster media (p-value = 0.000 <0.05). Health cadres can develop similar educational methods using poster media for other health education.